Screening Community Pharmacy Patients for Risk of Prescription Opioid Misuse. Issue 5 (September 2015) - Cochran, Gerald; Rubinstein, Jessica; Bacci, Jennifer L.; Ylioja, Thomas; Tarter, Ralph
Abstract : Objectives: This study tested screening feasibility and described the behavioral, mental, and physical health of patients filling prescriptions for opioid medications in the community pharmacy setting. Methods: We conducted a cross-sectional survey in rural/urban community pharmacies with adult noncancer patients. The survey included validated measures for opioid medication misuse risk, drug and alcohol use, and physical and mental health problems. Descriptive statistics were calculated, and bivariate and multivariable logistic regression evaluated relationships between opioid medication misuse risk and patient demographics, behavioral, mental, and physical health. Results: A total of 164 patients completed the survey (87% response rate), revealing positive screens for prescription opioid misuse risk (14.3%), illicit drug use (7.3%), hazardous alcohol use (21.4%), depression (25.8%), and posttraumatic stress disorder (PTSD; 17.1%). Bivariate analyses revealed increased odds of a positive opioid medication misuse risk score with a positive screen for illicit drug use in the previous year (odds ratio = 3.91; 95% confidence interval [CI], 1.05–14.63) and PTSD (odds ratio = 6.7; 95% CI, 2.54–17.69). In adjusted multivariable analyses, these relationships strengthened such that a positive screen for illicit drug use (adjusted odds ratio = 12.96; 95% CI, 2.18–76.9) and PTSD (adjusted odds ratio = 13.3; 95% CI, 3.48–50.66) increased odds for a positive opioid medication misuse risk score. Conclusions: Findings confirmed the feasibility of screening risk factors and positive opioid medication misuse risk among community pharmacy patients. Future research should validate these findings as a foundation to intervention development.